PERBEDAAN HASIL KONTROL PLAK SEBELUM DAN SESUDAH MELIHAT VIDEO TUTORIAL MODIFIED BASS TECHNIQUE KELAS V - Deru Marah Laut; Noor Alfiaty; Hera Nurnaningsih; Eliza Herijulianti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Basic Health Research (RISKESDAS, 2018) recorded the proportion of dental and mouth problems of 57.6%. The proportion of teeth brushing behavior was 2.8% correctly. Based on these data solutions are needed to improve people's behavior to brush their teeth properly to reduce the proportion of dental and mouth problems significantly. This study aims to determine the differences in the results of plaque control before and after watching the video tutorial on brushing modified bass technique teeth in fifth-grade students at SDN X Subang Regency. The research method is analytic. The sampling technique uses the purposive sampling technique (30 respondents). Data collection in this study was carried out direct observation of fifth-grade students at SDN X, by practicing how to brush their teeth after watching a video tutorial on brushing modified bass technique and direct examination of the health status of their teeth and mouth (Plaque Control). Statistical test results using t-paired tests with two-way hypothesis obtained the average results of brushing teeth at the first visit before seeing the video tutorial is 21% and after seeing the video tutorial is becoming to 13%. In the 2nd control plaque, an average score of 3% was obtained and in the 3rd control plaque, an average score of 1% was obtained. So there is a decrease in the control plaque results. By looking at the t value > t table, Ho's decision is rejected, and "Ha is accepted" meaning that there is a significant difference between the results of plaque control before and after watching the video tutorial on brushing modified bass technique in fifth-grade students of SDN X Subang Regency.